2021
DOI: 10.1002/anie.202014319
|View full text |Cite
|
Sign up to set email alerts
|

Photoactive Organic/Inorganic Hybrid Materials with Nanosegregated Donor–Acceptor Arrays

Abstract: The synthesis of the first mesogenic donor‐acceptor polyoxometalate (POM)‐based hybrid is herein described. The structural and electronic properties of the hybrid compound were evaluated through combination of small‐ and wide‐angle X‐ray scattering, optical microscopy, electrochemistry and photoluminescence. In the solid state, the compound behaves as a birefringent solid, displaying a lamellar organization in which double‐layers of POMs and bis(thiophene)thienothiophene organic donors alternate regularly. Not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In their work the authors coupled two moieties of a novel bis(thiophene)thienothiophene (BTTT) derivative to the bis-iodo aryl terminated Keggin POM-based hybrid platforms. 171 The authors reported a multi-layered lamellar structure of the mesophase consisting in the alternation of POM/TBA counter ion double layers and double sub-layers of tilted BTTT mesogens, isolated from each other by a continuum of molten aliphatic chains (Fig. 20).…”
Section: Nanostructured Pom-based Hybrid Materialsmentioning
confidence: 99%
“…In their work the authors coupled two moieties of a novel bis(thiophene)thienothiophene (BTTT) derivative to the bis-iodo aryl terminated Keggin POM-based hybrid platforms. 171 The authors reported a multi-layered lamellar structure of the mesophase consisting in the alternation of POM/TBA counter ion double layers and double sub-layers of tilted BTTT mesogens, isolated from each other by a continuum of molten aliphatic chains (Fig. 20).…”
Section: Nanostructured Pom-based Hybrid Materialsmentioning
confidence: 99%
“…Apart from chemical and electrochemical reactivity, the photoactivity of POMs has been known in the literature for several decades. [93][94][95][96][97] Particularly, in the presence of an efficient electron donor such as 2-propanol or benzyl alcohol, molybdenum (Mo) and tungsten (W) based salts with organoammonium counter ions readily undergo photochemical reduction in molecular solvents, resulting in the formation of intensely blue-coloured reduced molybdates or tungstates, the so-called heteropoly blues. [98][99][100] This reactivity can result in substrate oxidation or reduction and be used for a wide range of substrate molecules.…”
Section: Photochemistry Of Polyoxometalatesmentioning
confidence: 99%
“… Moreover, further introduction of rare-earth (RE) ions into the POT system will not only act as metal linkers between fundamental building units contributing to larger POTs (Figure S1b) , but also deliver their functionality into POT materials (e.g., magnetism or photoluminescence, etc. ). , On this basis, various organic–inorganic hybrid RE-inserted POTs (OIHREPOTs) have been obtained so far via a self-assembly strategy. For example, Zhao and colleagues reported a representative organometal and RE co-implanted tellurotungstate nanocluster, in which Sn­(CH 3 ) 2 2+ and Ce 3+ ions as metal linkers join eight tetralacunary Keggin {TeW 8 } and two monolacunary Lindqvist {CeW 5 } clusters together (Figure S1c).…”
Section: Introductionmentioning
confidence: 99%